2003
DOI: 10.1108/10662240310478187
|View full text |Cite
|
Sign up to set email alerts
|

Innovativeness and variety of Internet shopping

Abstract: A survey of 208 US Midwestern Internet users reveals, first, that the nature of Internet dhopping (IS) is a function of consumers’ domain specific IS Innovativeness, not only in regard to product purchasing (as has been previously observed) but also to visiting sites for product information. Second, IS innovativeness is positively associated with the variety of product classes shopped online, and this association is stronger with popular than with unpopular product classes. Third, the impact of IS innovativene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 26 publications
3
72
1
12
Order By: Relevance
“…In all four studies, the DSI was found to correlate positively with frequency of online shopping. Further, our earlier work (Blake et al, 2003) also found that the DSI was predictive of the range and variety of product/ service classes shopped. It appears, then, that domain specific innovators are especially likely to frequent new websites.…”
Section: Innovativenessmentioning
confidence: 99%
See 4 more Smart Citations
“…In all four studies, the DSI was found to correlate positively with frequency of online shopping. Further, our earlier work (Blake et al, 2003) also found that the DSI was predictive of the range and variety of product/ service classes shopped. It appears, then, that domain specific innovators are especially likely to frequent new websites.…”
Section: Innovativenessmentioning
confidence: 99%
“…The impact of innovativeness (as measured by the DSI) upon the probability of shopping online is apparent even when one's experience with the Internet is controlled (Blake et al, 2003;Citrin et al, 2000;Goldsmith, 2001). However, the contribution to online shopping of Internet experience may be modest when DSI is controlled (Blake et al, 2003).…”
Section: Internet Experiencementioning
confidence: 99%
See 3 more Smart Citations